Implementasi Weighted Product Untuk Penerimaan Karyawan - Anita Rahmawati; Yuli Astuti (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2018)
Development of resources on its human resources. For to to for to be taken taken taken taken taken taken taken taken. CV Rumahweb Indonesia is one of the companies engaged in the field of information technology associated with domain registration services and web hosting services. The data collection is currently using the system of administration and manual elections that take a long time to be able to determine the employees received. Criteria needed for the process of completion of exam questions, practical tests, work experience, communication and appearance. The first step is to enter data by way of interviewing the object of the problem that leads. From the process it takes a long time and a long goal that is not right. Requires a decision support system to handle it. In systems built using product weighting methods with the same criteria and can be used to process the data used. Thus, it can be used as a consideration. Keywords: weighted product, employee, decision support system